DESAIN BANGUNAN PANTAI SEAWALL TERHADAP TINGGI GELOMBANG (STUDI KASUS PANTAI PADANG) - Syahputra, Muhammad Noer (Inersia: Jurnal Teknik Sipil, 2020)
Padang Beach is one of the beaches in Sumatra that have an abrasion. Abrasion causes damage to public facilities in the region, the purpose of this research is to design a seawall beach building in the city of Padang Beach. The implementation method of research used with primary data processing is a direct field survey (Hs and Ts) while secondary data using wind data analysis methods, and the analysis of tidal data. Secondary data on this research is the wind data taken for 10 years (2010-2019) obtained from the Meteorological and Geophysical Agency of Meteorology (BMKG) and tidal data taken over the last 5 years (2015-2019) obtained from PT. Pelabuhan Indonesia II of Teluk Bayur. The outcome of the seawall research calculation has a length of 22.58 m, landmark elevation 5.31 m, and the building elevation of 9.31 m, the peak width of 4 m. Weight of seawall protective unit W = 4.152 tons, W/10 = 415.2 kg, W/200 = 21 kg, and the protective sum of each 10 m2 as much as 11 pieces.